2021
DOI: 10.1002/jbmr.4402
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline is associated with an accelerated rate of bone loss and increased fracture risk in women: a prospective study from the Canadian Multicentre Osteoporosis Study

Abstract: Cognitive decline and osteoporosis often coexist and some evidence suggests a causal link. However, there are no data on the longitudinal relationship between cognitive decline, bone loss and fracture risk, independent of aging. This study aimed to determine the association between: (i) cognitive decline and bone loss; and (ii) clinically significant cognitive decline (≥3 points) on Mini Mental State Examination (MMSE) over the first 5 years and subsequent fracture risk over the following 10 years. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Drugs targeting SLC13A5/INDY are now available and are reported to work in vitro [ 101 ] and in vivo [ 104 ]. Furthermore, bone is the main site of citrate storage in mammals, and bone demineralization is likely to release citrate in individuals with osteoporosis, which has recently been linked with dementia in humans [ 105 , 106 ].…”
Section: Citrate Transport and Its Role In Ageing And Diseasementioning
confidence: 99%
“…Drugs targeting SLC13A5/INDY are now available and are reported to work in vitro [ 101 ] and in vivo [ 104 ]. Furthermore, bone is the main site of citrate storage in mammals, and bone demineralization is likely to release citrate in individuals with osteoporosis, which has recently been linked with dementia in humans [ 105 , 106 ].…”
Section: Citrate Transport and Its Role In Ageing And Diseasementioning
confidence: 99%
“…Using the Canadian Multicentre Osteoporosis Study (CaMos), the relationship between cognitive decline, bone loss, and fracture risk was examined in 2361 participants (74% female) selected from the general population [60]. Cognition was assessed using the MMSE.…”
Section: Bone and Cognitionmentioning
confidence: 99%
“…Musculoskeletal and cognitive function declines often occur at the same time, for example with aging or in individuals with dementia [1][2][3]. Cognition is an intellectual or mental process via which organisms obtain knowledge and cognitive impairment (diminished intellectual and/or mental functioning) is associated with obesity [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent issue of the Journal of Bone and Mineral Research (JBMR), Bliuc and colleagues (1) reported an association of cognitive decline with bone loss and an increased risk of fracture in nondemented older women. They found that a decline in cognitive performance by 1% resulted in a decline in bone loss by 6% in long-term follow-up, providing possible evidence for the association between dementia and osteoporosis.…”
Section: To the Editormentioning
confidence: 99%